2015
DOI: 10.3390/molecules20059263
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Click Chemistry Applied to Dendrimer Synthesis

Abstract: Dendrimers are monodisperse polymers grown in a fractal manner from a central point. They are poised to become the cornerstone of nanoscale devices in several fields, ranging from biomedicine to light-harvesting. Technical difficulties in obtaining these molecules has slowed their transfer from academia to industry. In 2001, the arrival of the "click chemistry" concept gave the field a major boost. The flagship reaction, a modified Hüisgen cycloaddition, allowed researchers greater freedom in designing and bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(69 citation statements)
references
References 219 publications
(277 reference statements)
0
66
0
Order By: Relevance
“…However, their three key features including monodispersity, their multi-valency and their globular shape make them as potent nanotheranostic devices in biomedical fields (Arseneault et al 2015). Dendrimers can be designed with several reactive groups, facilitating surface modification.…”
Section: Dendrimersmentioning
confidence: 99%
“…However, their three key features including monodispersity, their multi-valency and their globular shape make them as potent nanotheranostic devices in biomedical fields (Arseneault et al 2015). Dendrimers can be designed with several reactive groups, facilitating surface modification.…”
Section: Dendrimersmentioning
confidence: 99%
“…Wei et al [74] used the feature of amphiphilic dendrimers [75] to form nanomicelles [76]. Using immunocompromised NSG mice (see [77,78] for mouse strain description), the authors found that tumor volume was reduced after treatment with Dox-loaded carriers while the mice retained body weight [74].…”
Section: Applications Of Nanotechnology To Life Sciencesmentioning
confidence: 99%
“…Dendrimers are outstanding candidates for template synthesis of nanoparticles because of their regular structure and chemical versatility. Dendrimers have three basic anatomical features: a core, repetitive branch units, and terminal functional groups . The physical and chemical properties of dendrimers depend strongly on the chemical structure of all three components as well as on the overall size and dimensionality of the dendrimer.…”
Section: Introductionmentioning
confidence: 99%